Effect Of Agitated Chicken-Droppings for in Situ Bioremediation of Pahs in Spend Engine-Oil Contaminated Soil (Journal of Bio-Science, 2021)
The populace are concern about how their environment is impacted by spend or used engine oil. The spills from spend engine oil posed serious problems to the land and aquatic habitats. Efficient methods but low-cost technique for remediating spends engine oil contaminated soil and restorations of soil fertility are being explored. In response to used engine oil pollution to the soil, the present investigation examined the comparative biodegradation level of spend engine oil contaminated soil using fermented chicken droppings. The soil sample was collected from the uncontaminated site 10 cm below ground level. The sandy/loam soil was sieved with 2.5 mm mesh. A 4 kg of the soil was weighed into each bucket and contaminated with spend engine oil, the soil was contaminated with 150 ml of the spend engine oil at a ratio of 1:27. A 27 kg of chicken droppings was mixed with 27 liters of water in a ratio of 1 kg: 1L. The mixture was left for 7days to ferment and increase the microbial load. The contaminated soil was irrigated using an experimental design that included uncontaminated soil that was irrigated using normal water (positive control), contaminated soil that was irrigated using normal water (negative control) and contaminated soil irrigated using fermented chicken droppings (test). Five hundred mL of the chicken droppings mixture was used to irrigate the soil for 21 days at an interval of 3 days per irrigation. Thereafter, the irrigated soil was screened with gas chromatography linked with mass spectroscopy. There was an observed change in contaminant concentration without fermented chicken droppings. The percentage of differences in the concentrations was recorded in × 10–5% with the presence of Naphthalene and Acenaphthylene with the percent difference of 2.0 × 10–5% and 5.0 × 10– 5%. Result revealed an appreciable decrease in PAHs level compared to the positive and negative control. The findings suggest the positive effect and rapid uptake of the contaminant in the application of fermented chicken droppings.J. Bio-Sci. 29(1): 01-09, 2021 (June)